NDFP declaration and program of action for the rights, protection and welfare of children (Quezon City, Philippines : NDFP-Monitoring Committee, 2012)
This book contained data on the status and conditions of Filipino children and comprehensive position of the NDFP on their rights and welfare.
The NDFP's defense of the rights of the Filipino Child -- NDFP Declaration and program of action for the rights, protection and welfare of children -- Profile of Filipino children -- The NDFP declaration and program of action for Filipino children -- CPDF statement congratulating the launching of the NDFP declaration and program of action for the rights, protection and welfare of children -- The revolutionary movement's advocacy and protection of children's right and welfare -- The entire revolutionary forces in NEMR firmly adhere to the NDFP declaration and program of action for the rights, protection and welfare of the children -- Uphold and protect the rights of Filipino children.
Keywords: CHILDRE'S RIGHT -- PHILIPPINES